Financial Restructuring to Sustain Recovery - Seki, Yuta; Herring, Richard J.; Baily, Martin Neil (Book collections on Project MUSE., 2013)
How much financial regulation will adequately reduce future systemic threats to the financial sector? To what extent can international authorities legally oversee the financial activities and outcomes of other transnational entities? Can macroprudential policy be aligned successfully with monetary policy to weather another boom-bust cycle? Editors Martin Neil Baily, Richard Herring, and Yuta Seki envision a global policy response to the financial crisis, designed to maintain sector-wide economic growth and improve profitability, rather than a response limited to secure only the stren.